Magnetic domains and the process of technical magnetization - Sharipov Mirzo; Ergasheva Nilufar; Raupova Iroda; Fayzieva Zarifa; Zokirova Zarkhal (EPJ Web of Conferences)
This article presents the results of the formation of a domain structure and the process of technical magnetization of weak ferromagnets. It has been determined that for a given film thickness, the characteristic dimensions of the domain structure depend on the energy density of domain boundaries and the magnetic dipole energy density.